Kuĺ 1, a mesolithic site from South-West Belorussiav - Vashanau, Aliaksandr M. (Acta Archaeologica Lodziensia, 2018)
Kuĺ 1 settlement is located 5.1 km to the west of Sviatica village, Liachavičy District, Brest Region (southwestern Belorussia). An area of 81 m2 was excavated at the site in 2006. The obtained archaeological assemblage consists of 286 flint artifacts. Cores for blades and flakes are represented by single- (2 pieces), double- (3) and multiplatform (3) ones as well as four fragments. Tool-set contains various types of burins (12), end-scrapers (3), a scraper (1), truncated blades (3), adzes (3). A bladelet with truncated base is the only microlith in the assemblage. It is possible to attribute the assemblage to Kudlaevka culture based on peculiarities of flintworking technology and morphology of tools.